A light-scattering study of highly refractive, irregularly shaped MoS2 particles. (February 2020) - Gautam, Prakash; Sorensen, Christopher M.
Highlights: Mie theory adequately describes scattering by irregularly shaped particles with large refractive index. Enhanced backscattering is quenched when 2κπR/λ is large. Guinier analysis of light scattering yields intensity weighted mean sizes of reasonable accuracy for any shape. Abstract: We present measurements of light scattering intensity from aerosolized, micron sized, irregularly shaped, molybdenum disulfide (MoS2 ) particles in order to study the effects of a refractive index, m = n + iκ, with large real and imaginary parts. Light scattering was measured over a range of angles from 0.32° to 157°. Calibration was achieved by scattering with micron sized, spherical silica particles. Light scattering for both particle types was compared to theoretical Mie scattering calculations using size distributions determined by an aerodynamic particle sizer. Effects of the intensity weighted size distribution are discussed. We find that scattering by these irregularly shaped, highly refractive particles is well described by Mie scattering. We also find that when the quantity κkR, where kR = 2πR/λ is the size parameter, is greater than one, there is no enhancement in the backscattering. Finally, we show that Guinier analysis of light scattering by highly refractive particles yields intensity weighted mean sizes of reasonable accuracy for any shape.